South Africa in world history - Berger, Iris 1941- (The new Oxford world history, 2009)
South Africa in World History discusses the history of South Africa from the early centuries of the Common Era to the present-day and addresses broad themes of world history such as colonialism, white settlement, nationalism and reconciliation.